The effects of competition regulations on mobile telecommunication markets - Ioan Lucian ALEXA (Theoretical and Applied Economics, 2015)

(untitled)
This paper is based on the classic economics hypothesis that the presence of a reduced number of suppliers on a market can provide them a larger negotiation power towards consumers, thus being able to abuse this power in the disadvantage of consumers. Because the telecommunications market is characterized by a reduced number of operators due to its specific features, the present paper wants to analyze what are the implications on consumers, for the perspective of the costs they endure and what effects have the regulations on this market for the consumers from Romania. The paper analyzes how the reduction of interconnection tariffs affects the price structure of mobile communications, penetration rate of mobile communications, the degree of usage of these services and the evolution of the number of operators in the market, comparing the evolution of these variables before and after the 2009 European Commission proposals. Also the paper aims to determine the demand equation for mobile communications services through a panel model that analyzes 21 of the member states of the European Union, to identify the main factors that have influence on the demand and also to determine the price elasticity of demand.